Analysis of Factors Related To The Implementation of Balikpapan Mayor Regulation No. 9 of 2020 Concerning The Prevention and Control of Dengue Hemorrhagic Fever in Balikpapan City - Yogik Wahyudianto; Ratno Adrianto; Ratih Wirapuspita W (Eduvest - Journal of Universal Studies, 2025)
Dengue Hemorrhagic Fever (DHF) remains a pressing health concern in Balikpapan, with 1,081 reported cases in 2022, despite the enforcement of Mayor Regulation No. 9/2020 aimed at prevention. This study analyzed the influence of communication, resources, and disposition on the regulation’s implementation in South Balikpapan through an analytical cross-sectional survey of 189 jumantik cadres, using chi-square tests and multivariate logistic regression. Findings revealed significant relationships between implementation and communication (p = 0.008), resources (p = 0.000; OR = 8.272), and disposition (p = 0.001), with resources identified as the most influential factor. The results highlight the importance of improving resource allocation, establishing structured communication, and motivating cadres to enhance dengue prevention efforts, while recommending future studies to incorporate technological tools like GIS and assess long-term policy outcomes.